Elucidating the immunomodulatory roles and mechanisms of CUL4B in the immune system: a comprehensive review - He, Siyu; Wang, Ziyue; Zhu, Yinan; Sun, Mingfang; Lin, Xuyong (Frontiers in Immunology, 2025)
Cullin 4B (CUL4B), a pivotal member of the Cullins protein family, plays a crucial role in immune regulation and has garnered significant research attention. CUL4B, through the Cullin 4B-RING E3 ubiquitin ligase (CRL4B) complex, regulates CD4+ T cell differentiation, fostering a balance between TH1 and TH2 subsets, and expedites DNA damage repair to bolster T cell persistence. In B cells, CUL4B upregulation stimulates immune responses but is linked to an unfavorable prognosis in lymphoma. In innate immunity, CUL4B modulates Toll-like receptor (TLR)-mediated anti-inflammatory responses, enhancing macrophage migration and adhesion. CUL4B also plays a role in potentiating anti-tumor immunity by restricting the activity of myeloid-derived suppressor cells (MDSCs). In disease pathogenesis, CUL4B limits MDSCs to enhance anti-tumor effects, and its inhibition in experimental autoimmune encephalomyelitis (EAE) models have demonstrated beneficial effects, underscoring its potential therapeutic significance in autoimmune diseases. Furthermore, CUL4B is involved in various immune-related cancers and inflammation, including pleural mesothelioma, human osteosarcoma, and colitis-associated cancer. In metabolic diseases, CUL4B regulates adipose tissue and insulin sensitivity, with its depletion improving metabolic phenotypes. This review highlights the pivotal role of CUL4B in maintaining immune homeostasis and provides novel perspectives and insights into the understanding and development of treatments for immune-related disorders.